How Do I Examine Nonmotor Aspects of Parkinson's Disease? What Not to Miss and What to Ignore?. Issue 3 (1st September 2014) - Todorova, Antoniya; Martin, Anne; Chaudhuri, K. Ray
Abstract : View Supplementary Video 1 Abstract: Nonmotor symptoms (NMS) of Parkinson's disease are a wide range of symptoms that occur well before the onset of the motor syndrome and are present right until the end of life. NMS could be classified to several types and broadly belong to dopaminergic, nondopaminergic, drug‐induced subgroups and those related to motor response fluctuations. NMS are relatively under‐recognized in clinical practice and can be rapidly assessed in the clinic by asking patients to complete the Non‐Motor Symptoms Questionnaire (which can be downloaded fromhttp://www.movementdisorders.org/MDS/Education/Rating-Scales/Rating-Scales-By-Disorder.htm ) while they are waiting to be seen. The consultation thereafter can cover the important aspects of the symptoms that have been declared by the patient in addition to the management of the motor symptoms.